IMPLEMENTASI FATWA DSN-MUI NO: 86/ DSN-MUI/ XII/ 2012 TENTANG HADIAH DALAM PENGHIMPUNAN DANA - M. Ridwan Setiawan; Rahmawati Rahmawati; Wahidin Wahidin (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2019)
The fatwa of the DSN-MUI is the answer issued by the National Sharia Council-Indonesian Ulama Council (DSN-MUI) as an explanation of the sharia law for people who ask questions about problems in the field of Islamic economics. The goal is that sharia principles in the fatwa be implemented in contracts for Islamic Financial Institutions (LKS). However, public statements often arise that giving gifts to Islamic banks and conventional banks is the same as the scheme and method of giving. This study aims to see how the mechanism and suitability of DSN-MUI fatwa No: 86 / DSN-MUI / XII / 2012 concerning Prizes in Fundraising (Study at Bank Muamalat KCP Parepare). The results of the research can be stated that at Muamalat bank, KCP Parepare has two savings programs with prizes, the first is prizes with prizes, customers deposit funds in the amount set by the bank for a predetermined period of time, second savings plan with prizes, customers deposit money at the beginning of the amount of money that has been determined by saving each month in the amount determined by the bank, the greater the amount of money saved the greater the number of prizes received. In the DSN-MUI fatwa related to the awarding of prizes there are 3 provisions related to this, namely the first provision related to prizes, the two provisions relating to the determination of receipt of implemented prizes according to fatwa, third not the provisions concerning prizes in deposits of Third Party Funds (DPK) all points in this fatwa implemented specifically on the third point that reads should not be the norm (habit, 'urf), that the' urf or custom prohibited by DSN-MUI in the fatwa prize aims to avoid changing intentions from the customer, intention to save become the desire to get something without effort.